Rare Cause of Sphincter of Oddi Dysfunction and Double Duct Sign - Goel, Akash; Singla, Vikas; Bopanna, Sawan; Singh, Pankaj; Shawl, Muzaffer Rashid (Journal of Digestive Endoscopy, 2024)
Double duct sign on imaging is defined as dilated common bile duct and pancreatic duct till ampulla and is usually associated with an ampullary obstruction likely periampullary malignancy. Sphincter of Oddi dysfunction is an uncommon cause of double duct sign. In the present case, we are discussing a rare cause of Sphincter of Oddi dysfunction with double duct sign.
Keywords: Double Duct Sign; Sphincter of Oddi Dysfunction; Endoscopic Ultrasound; Morphine; Opium